Reorganización urbana en el microcentro de Neiva: solución para la informalidad comercial (2022)
In the traditional center o f the city of Neiva, the appropriation of public space by commercial informality has increased due to different factors such as school dropout, unemployment, lack of opportunities, among others. This situation has affected pedestrian and road mobility, cre ating not only great congestion on the site, but also interrupting the interrelation between the inhabitants, preventing their circulation and threatening their own safety. Therefore, the objective of this research is to recognize the causes that encourage the informal vendor to cover more space over the years, taking into account the activities that occur in the environment in which they are, so that it is possible to identify the profile of informal workers. Likewise, it is intended to generate a spatial proposal which allows optimizing and ordering mobility in the city center, considering the respective importance of public space, and at the same time, understanding the social dynamics that is presented in order to provide the inhabitants of Neiva the rig ht to a city.